(untitled) (Swiss Medical Weekly, 2014)
Tumour angiogenesis plays a key role in the pathogenesis and progression of haematological malignancies. Thereby, pro- and anti-angiogenic growth factors and cytokines regulate the angiogenic process. The most important growth factor, vascular endothelial growth factor (VEGF) and its signaling through its receptors 1 and 2, is not only involved in solid tumours, but there is also emerging evidence that tumour progression in haematological malignancies also depends on the induction of new blood vessel formation. The evidence supporting this theory includes the finding of increased bone marrow microvessel density and increased levels of plasma pro-angiogenic cytokines. Leukaemia cells interact with surrounding host cells and extracellular matrix, this crosstalk affecting the most important aspects of the malignant phenotype. The pathophysiology of leukaemia induced angiogenesis involves both direct production of angiogenic cytokines by leukaemia cells and their interaction with bone marrow microenvironment. The inhibition of VEGF signalling by monoclonal antibodies or small molecules (kinase inhibitors) has already been successfully used for the treatment of different cancer entities, and multiple new drugs are being tested. This review summarises recent advances in the basic understanding of the role of angiogenesis in haematological malignancies and the translation of such basic findings into clinical studies.